Violet and blue light blocking intraocular lenses: photoprotection versus photoreception. Issue 6 (18th May 2006) - Mainster, M A
Abstract : Aim: To analyse how intraocular lens (IOL) chromophores affect retinal photoprotection and the sensitivity of scotopic vision, melanopsin photoreception, and melatonin suppression. Methods: Transmittance spectra of IOLs, high pass spectral filters, human crystalline lenses, and sunglasses are used with spectral data for acute ultraviolet (UV)-blue photic retinopathy ("blue light hazard" phototoxicity), aphakic scotopic luminous efficiency, melanopsin sensitivity, and melatonin suppression to compute the effect of spectral filters on retinal photoprotection, scotopic sensitivity, and circadian photoentrainment. Results: Retinal photoprotection increases and photoreception decreases as high pass filters progressively attenuate additional short wavelength light. Violet blocking IOLs reduce retinal exposure to UV (200–400 nm) radiation and violet (400–440 nm) light. Blue blocking IOLs attenuate blue (440–500 nm) and shorter wavelength optical radiation. Blue blocking IOLs theoretically provide better photoprotection but worse photoreception than conventional UV only blocking IOLs. Violet blocking IOLs offer similar UV-blue photoprotection but better scotopic and melanopsin photoreception than blue blocking IOLs. Sunglasses provide roughly 50% more UV-blue photoprotection than either violet or blue blocking IOLs. Conclusions: Action spectra for most retinal photosensitisers increase or peak in the violet part of the spectrum. Melanopsin, melatonin suppression, and rhodopsin sensitivities are all maximal in the blue part of the spectrum. Scotopic sensitivity and circadian photoentrainment decline with ageing. UV blocking IOLs provide older adults with the best possible rhodopsin and melanopsin sensitivity. Blue and violet blocking IOLs provide less photoprotection than middle aged crystalline lenses, which do not prevent age related macular degeneration (AMD). Thus, pseudophakes should wear sunglasses in bright environments if the unproved phototoxicity-AMD hypothesis is valid.